Effectiveness of cardiopulmonary bypass for radical resection of giant middle mediastinal paraganglioma - Nicola Rotolo; Andrea Imperatori; Luca Filipponi; Federica Torchio; Matteo Matteucci; Andrea Musazzi (Journal of Cardiovascular and Thoracic Research)
A non-functional middle mediastinal paraganglioma is a rare entity. We describe a case of a 67-year-old woman with a diagnosis of a big mediastinal paraganglioma by endobronchial ultrasound transbronchial needle aspiration after chest CT and 18F-fluorodeoxyglucose positron-emission tomography. The nine centimeter in length tumor was located between the superior vena cava and the posterior portion of the ascending aorta, compressing the left atrium and the trachea and main left bronchus, posteriorly, surrounding the right pulmonary artery. Uniportal right video-thoracoscopic biopsy was unconclusive and complicated by severe hemorrhage, however controlled. Surgical resection was performed via a trans-sternal trans-pericardial approach followed by cardiopulmonary bypass and ascending aorta resection which allows an excellent exposure and greater control of great vessels and heart. Complete resection of the tumor was achieved without perioperative complication except for the left vocal cord palsy. Twelve months late the patient is disease free and in good general conditions.